2021
DOI: 10.1186/s12889-021-10551-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between daily total physical activity and risk of cardiovascular disease among hypertensive patients: a 10-year prospective cohort study in China

Abstract: Background The effect of high levels of physical activity and relationship between daily total physical activity and the risk of cardiovascular disease (CVD) among hypertensive people were not clear. This study aimed to explore the optimum level of physical activity for CVD prevention. Methods Data used in the present study was derived from the sub-study of China Kadoorie Biobank study (CKB) in Jiangsu province of China. The CKB was a prospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…The source of this constructive interaction is difficult to resolve further without more precise estimates of exercise. For example, Zhou et al 48 recently observed a curvilinear relationship between an estimate of total daily activity, including commuting and work-related activity, and CVD incidence in a large sample of hypertensive adults. Mixed exercise has been promoted by the American Heart Association as reducing CVD risk 49 ; but, without a comprehensive tally of exercise types from participants, we can only speculate that the addition of dog walking may have yielded a mixed exercise program in this sample.…”
Section: Discussionmentioning
confidence: 99%
“…The source of this constructive interaction is difficult to resolve further without more precise estimates of exercise. For example, Zhou et al 48 recently observed a curvilinear relationship between an estimate of total daily activity, including commuting and work-related activity, and CVD incidence in a large sample of hypertensive adults. Mixed exercise has been promoted by the American Heart Association as reducing CVD risk 49 ; but, without a comprehensive tally of exercise types from participants, we can only speculate that the addition of dog walking may have yielded a mixed exercise program in this sample.…”
Section: Discussionmentioning
confidence: 99%
“…The source of the constructive interaction is di cult to further resolve without more precise estimates of exercise levels. For example, Zhou et al 47 recently observed a curvilinear relationship between an estimate of total daily activity, including commuting-and work-related activity, and CVD incidence in a large sample of hypertensive adults. Mixed exercise has been promoted by the American Heart Association as reducing CVD risk 48 , but without a comprehensive tally of exercise types from participants, we can only speculate that the addition of dog walking may have yielded a mixed exercise program in this sample.…”
Section: Discussionmentioning
confidence: 99%
“…Destaca-se a importância de programas voltados às pessoas idosas, posto que possuem fatores de risco cardiovascular diversos (ALVAREZ-ALVAREZ et al, 2020;MORALES;HERNÁNDEZ;PÉREZ, 2014;CARVALHO et al, 2017;CÂMARA et al, 2014;CASSIANO et al, 2020;CICHOCKI et al, 2017;ZHOU;SU;TAO, 2021;HIERREZULO;ÁLVAREZ;MONJE, 2021), com destaque para alguns deles, que carecem de maior atenção, incentivando um processo de envelhecimento saudável, no qual pessoas idosas mantémse funcionalmente preservadas.…”
Section: Variáveisunclassified